Luncheon - Trinidad - (:unkn) unknown (My University, 2009)
A group of labourers of East Indian origin taking a break from their toil in the fields to have lunch.
Colour: Black and white; Style: Landscape; Bordered, Divided
Keywords: Postcards; Trinidad and Tobago; East Indians--Trinidad and Tobago; Working class--Trinidad and Tobago; Men--Trinidad and Tobago; Women, East Indian--Trinidad and Tobago; Luncheons--Trinidad and Tobago; Blue collar workers--Trinidad and Tobago; Headgear--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago